Lack of STAT1 co-operative DNA binding protects against adverse cardiac remodelling in acute myocardial infarction - Doudin, Asmma; Riebeling, Theresa; Staab, Julia; Menon, Priyanka Rajeev; Lühder, Fred; Wirths, Oliver; Vinkemeier, Uwe; Ivetic, Aleksandar; Meyer, Thomas (Frontiers in Cardiovascular Medicine, 2023)
In this study, we addressed the functional significance of co-operative DNA binding of the cytokine-driven transcription factor STAT1 (signal transducer and activator of transcription 1) in an experimental murine model of acute myocardial infarction (MI). STAT1 knock-in mice expressing a phenylalanine-to-alanine substitution at position 77 in the STAT1 amino-terminal domain were examined for the early clinical effects produced by ligation of the left anterior descending coronary artery (LAD), an established model for MI. The F77A mutation has been previously reported to disrupt amino-terminal interactions between adjacent STAT1 dimers resulting in impaired tetramerization and defective co-operative binding on DNA, while leaving other protein functions unaffected Our results demonstrate that a loss of STAT1 tetramer stabilization improves survival of adult male mice and ameliorates left ventricular dysfunction in female mice, as determined echocardiographically by an increased ejection fraction and a reduced left intra-ventricular diameter. We found that the ratio of STAT3 to STAT1 protein level was higher in the infarcted tissue in knock-in mice as compared to wild-type (WT) mice, which was accompanied by an enhanced infiltration of immune cells in the infarcted area, as determined by histology. Additionally, RNA sequencing of the infarcted tissue 24 hours after LAD ligation revealed an upregulation of immune-responsive inflammatory genes in the knock-in mice, as compared to their WT littermates. Concomitantly, genes involved in oxidative phosphorylation and other metabolic pathways showed a significantly more pronounced downregulation in the infarcted tissue from STAT1F77A/F77A mice than in WT animals. Based on our results, we propose that dysfunctional STAT1 signalling owing to a lack of oligomerisation results in a compensatory increase in STAT3 expression and promotes early infiltration of immune cells in the infarcted area, which has beneficial effects on left ventricular remodelling in early MI following LAD ligation.